Early Yield and Economical Study of Pogostemon Cablinas Intercrop in Young Cocoa (Theobroma cacaoL.) - Adi Prawoto; M Sholeh N.P (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2006)
Pogostemon cablinis an important source of volatile oil for pharmaceutical and cosmetical products. Agronomical aspect of this commodity needs open ecosystem, but for certain level of shading, this crop may yield economically. A study to evaluate the effect of P. cablinintercropped on young cocoa farm, had been conducted during 2005, in Kaliwining Experimental Station of Indonesian Coffee and Cocoa Research Institute (ICCRI) 45 m above sea level, D climate type (Schmidt and Fergusson), and on low gley humic soil. The experiment was arranged in factorial and the field design was split plot replicated three times. The main plot was no shade tree, shade of Leucaena glauca and Areca catechuwhile the subsplots were fertilizer dose (per ha/year), i.e. (P0) without fertilizer; (P1) 140 kg Urea, 35 kg SP-36, 70 kg KCl; (P2) 280 kg Urea, 70 kg SP-36,140 kg KCl; and (P3) 560 kg Urea, 140 kg SP-36, 280 kg KCl. The result showed that P. cablin cultivation without shading gave better growth and yield than the shading treatment; meanwhile Leucaenashading showed better growth and early yield than the A. catechushading. Fertilizer rate of P1 produced highest leaf weight and oil yield, although P3 possessed the highest growth variables of plant height, stem diameter, number of leaves, leaf area and chlorophyll content. For the dry weight biomass variable, highest yield was obtained from no shade tree and P1 treatment. Using chromatography gas analysis, retention time of patchouly alcohol is 15—18 minutes, it was found that the content was influenced by shading treatment, i.e. 25.15% in monoculture, 28.73% in Leucaena and 25.21% in A. catechutreatment. For the oil viscosity variable, the monoculture treatment showed the highest value (23.21 centipoise), followed by A. catechu(11.60 centipoise) and Leucaenatreatment (8.65 centipoise). Intercropping of P. cablinwith young cacao did not show negative effect on young cacao growth. This study demonstrated that pre-cropping ofP. cablinin young cacao provided opportunity to farmers to have additional income, the benefit cost ratio (B/C) for Leucaenatreatment 1.00–1.35 depend on dose of fertilizer, while for A. catechutreatment gave no profit (B/C 0.59–1.03 depend on fertilizer dose). Meanwhile, P. cablinmonoculture cultivation gave B/C 1.44–2.71. Key Words: Pogostemon cablin, Theobroma cacao,Leucaena glauca, Areca catechu, intercropping, patchouly alcohol, B/C ratio, fertilizer.